2001
DOI: 10.1007/bf02234464
|View full text |Cite
|
Sign up to set email alerts
|

Identification of extracapsular invasion of the metastatic lymph nodes as a useful prognostic sign in patients with resectable colorectal cancer

Abstract: It is the thesis of this article that the identification of extracapsular invasion of the metastatic lymph nodes can be taken as a useful prognostic sign in patients with resectable colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 9 publications
0
36
0
1
Order By: Relevance
“…Many investigators have reported that, in patients with various malignancies, the pathological characteristics of metastatic nodes could be associated with survival [2][3][4][5][6]: however, some of the populations [3,6] might not be selected properly in the previous studies. In patients with localized gastric cancer, the number of metastatic nodes and the presence of serosal invasion were the strongest prognosticators, the latter being associated with peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have reported that, in patients with various malignancies, the pathological characteristics of metastatic nodes could be associated with survival [2][3][4][5][6]: however, some of the populations [3,6] might not be selected properly in the previous studies. In patients with localized gastric cancer, the number of metastatic nodes and the presence of serosal invasion were the strongest prognosticators, the latter being associated with peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have assessed the correlation between the histology of lymph node metastasis and patients' prognoses in various types of tumors, including breast and colorectal tumors [4,5]. The presence of extracapsular invasion (ECI) has been reported to be a signifi cant prognostic factor in patients with gastric cancer [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…4,12 ECE of lymph node metastasis has been shown to be prognostic in patients with malignancies of breast, gastrointestinal tract, prostate, and penis. [16][17][18][19] To our knowledge, the only published reports on the significance of ECE in bladder cancer are from the University of Bern, Switzerland. [4][5][6] They found that ECE was an independent prognostic factor for RFS in a retrospective analysis from 1985-2000 that included 101 patients with lymph node metastasis at time of radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several manuscripts have shown that delays of more than 12 weeks bewteen TURBT and RC significantly correlated with higher rates of nonorgan confined disease and with cancer-specific and overall mortality. [7][8][9][10][11] These findings cannot be generalized to patients with bladder cancer treated with PC because this constitutes a select category of patients with a favourable disease profile and presumably better prognostic potential. To date, no study has investigated the impact of delaying PC on disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that delaying RC is significantly associated with worse outcome. [7][8][9][10][11] However, no studies have evaluated treatment delays among patients who underwent PC. The goal of the present study was to investigate variables associated with delays between transurethral resection of bladder tumours (TURBT) and PC and to examine the impact of such delays on disease outcome.…”
Section: Discussionmentioning
confidence: 99%